Ethics of Professional Competence in Accounting and Accounting Practice - Inyang, William Smart; Oboh, John Ogenyi; Nwabuikem, Rex Tobechukwu (Current Topics on Business, Economics and Finance Vol. 6, 2023)
This research is anchored on the argument that the application of ethics of integrity, ethics of objectivity, ethics of professional behaviour and ethics of professional competence and due care has not significantly improved the accounting practices of corporate organizations in Nigeria. Ethics in the accounting profession was for long associated only with accounting scholars, investors and accounting bodies around the world. The general notion to this is the public perception that organizations should strive towards ethical transparency. The concept of ethics simply deals with how decisions affect other people and organizations. The study employed stratified and simple random sampling techniques to develop the sample components. The goal of stratified random sampling is to achieve desired representation from various sub-groups in the population. Due to large size of the target population, 269 participants were accessible. Taro Yamane formula was used to arrive at the population sample of this study. The questionnaires were administered to the registered members of the ICAN District Society in Calabar, Nigeria and data generated from the questionnaires were analysed using IBM SPSS V.20. The results revealed a significantly negative relationship between ethical thoughts and the accounting practices of corporate organizations in Nigeria. On the basis of the findings, the study recommended the following among others: Professional accountants as custodians and producers of accounting information should adhere to the codes of professional best practices issued by relevant professional bodies. It is complex to the extent that there is the likelihood that a conflict of interest might arise due to the multiplicity of end users of accounting information. Consequently, the continuum of interested parties; Management, shareholders, creditors, employees amongst others puts the financial statement and its preparers in a complex environment. Every organisation in Nigeria should set up an ethics department to make sure that all practises, including financial reporting, adhere to the codes of ethics. The Board of Directors and Audit Committees should be made up of individuals with financial knowledge, demonstrated integrity, and corporate experience. Greater efforts should be made by the appropriate professional bodies to review the various ethical codes that direct members' conduct or behaviour in practise. Additionally, widespread education combined with harsher penalties for professional misconduct may be a solution.